EMPLOYEE SATISFACTION MODERATES THE EFFECTS OF GREEN SUPPLY CHAIN MANAGEMENT, LEADERSHIP AND ORGANIZATIONAL CULTURE ON CORPORATE PERFORMANCE - Banjarnahor, Erliana; Yvonne Augustine Sudibyo (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
This research aims to determine if employee satisfaction mitigates the detrimental effects that organizational culture, leadership, and GSCM have on corporate performance. For this purposeful convenience sampling, the research population is an industrial and commercial firm in Indonesia. The primary source of the data used is from surveys that were gathered using Google Forms. The sample for the study consisted of 102 people. The statistical analysis in this study used structural equation modeling using partial least squares. This study expands the GSCM's set of indicators. The study's findings demonstrate that GSCM, leadership, and organizational culture all have an impact on business performance. But only the impact of organizational culture—not the impact of GSCM or leadership—on performance is tempered by employee satisfaction. The study includes ramifications for manufacturing and trading companies, such as the requirement for a strong organizational culture, strong leadership, and the application of a GSCM strategy. The research tools or GSCM indicators are what set this study apart from others. The amount of respondents to the survey is one of this study's shortcomings, hence it is recommended that future research use more samples. Keywords: Organizational culture, leadership, green supply chain management, and employee satisfaction